2021
DOI: 10.2967/jnumed.121.262863
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of In Vivo Imaging of Fibroblast Activation Protein in Human Arterial Walls

Abstract: Increased expression of fibroblast activating protein (FAP) in fibrous caps may contribute to progression of atherosclerotic plaques. Methods Forty-one patients who underwent gallium-68conjugated quinoline-based FAP inhibitor ( 68 Ga-FAPI-04) PET/CT for non-cardiovascular indications were retrospectively analyzed. Correlations were assessed between the uptake of 68 Ga-FAPI-04 in large arterial walls (SUVmax and target-to-background ratio, TBR) and degree of calcification and cardiovascular risk factors. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“… 28 Similar results of a large variety of uptake in oncology patients scanned with FAPI-PET have also been reported for the vasculature. 29 As such, given the lower ICC for the blood pool along with previous reports showing a potential interaction in cardio-oncology settings, unaffected liver parenchyma may be better suited for TBR calculations.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Similar results of a large variety of uptake in oncology patients scanned with FAPI-PET have also been reported for the vasculature. 29 As such, given the lower ICC for the blood pool along with previous reports showing a potential interaction in cardio-oncology settings, unaffected liver parenchyma may be better suited for TBR calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that left ventricular 68 Ga-FAPI uptake correlated with the presence of cardiovascular risk factors such as overweight status (odds ratio, 2.6; P 5 0.023), type 2 diabetes (odds ratio, 2.9; P 5 0.041), and histories of platinum-based chemotherapy (odds ratio, 3.0; P 5 0.034) and chest radiation (odds ratio, 3.5; P 5 0.024) (68). Finally, a retrospective analysis of 68 Ga-FAPI PET/CT images obtained for noncardiovascular indications showed that focal arterial uptake of the tracer correlated negatively with calcification (r 5 20.27, P , 0.01) (69). Several ongoing clinical trials seek to establish the role of FAPI imaging to detect post-MI cardiac fibrosis (NCT04803864, NCT04723953).…”
Section: Radiotracers For Cardiovascular Fibrosis Imagingmentioning
confidence: 94%
“…Immunohistochemical labeling of carotid plaques also found prominent FAPI expression in thin fibrous caps compared to moderate expression in thick caps. 54 As yet, no studies have assessed coronary 68 Ga-FAPI uptake although there is potential for this radiotracer to assess atherosclerotic fibroblast activity in other vascular territories.…”
Section: Myocardial Viability and Functional Recoverymentioning
confidence: 99%
“…Elevated uptake occurred in non‐calcified arterial segments when compared to advanced chronic lesions and increased arterial uptake in patients with more cardiovascular risk factors. Immunohistochemical labeling of carotid plaques also found prominent FAPI expression in thin fibrous caps compared to moderate expression in thick caps 54 . As yet, no studies have assessed coronary 68 Ga‐FAPI uptake although there is potential for this radiotracer to assess atherosclerotic fibroblast activity in other vascular territories.…”
Section: Pet‐mri and Myocardial Imaging In Coronary Artery Diseasementioning
confidence: 99%